Emerging economies crises: lessons from the 1990's - Strašek, Sebastjan (Managing global transitions, 2007)
The paper examines the financial crises of the 1990s. They represent a new kind of crises, as they do not seem to conform to the so-called first generation and second generation literature on currency crises. The outburst of the Asian crises brought a new challenge for economic policy. The attention has been placed on the self-fulfilling character of the speculative attacks and microeconomic weaknesses. The first part of the paper reviews the recent theoretical literature on financial crises, the second part addresses some lessons for emerging economies. The authors consider the policies to manage financial crises and reduce the risks associated with them.
Keywords: finance; finančne krize; preventiva; makroekonomija; finančni instrumenti; finančno odločanje; economics; ekonomija